Formation of concepts in teaching students with clip thinking - Косьміна, В. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2019)
The article is devoted to a description of the formation of concepts in teaching students with clip thinking. The concept is defined as a culturally significant unit of the mental level, reflecting nationally specific information. In the concept, the word, language and non-verbal behavior are combined into an inextricable whole. It was found that concepts in the educational process can be used as a unit of training, selection, and organization of language (lexical) material.When forming concepts, a student with clip thinking will be able to realize the ability to find the necessary information in its most diverse sources and at the same time to master the ability to systematize, explain, and also understand the features of the use and compatibility of certain language units in the Ukrainian language, while expanding knowledge about the Ukrainian language picture of the world, to form their own “secondary language personality”. The work on the formation of conceptual and artistic concepts can help students with a prevailing clip type of thinking learn a new language, increase motivation, learn to better understand and feel both the cultural traditions of the speakers of the studied language and their own. Using the formation of concepts during training develops the students' ability to select, classify, systematize the necessary language material depending on the purpose and situation of communication; to improve and implement the compensatory skills of students; teach them how to build coherent discourse and select the right language strategies for its implementation. All this contributes to a clear organization of the educational process, ensures the effective formation of the intercultural competence of students.